Modelling library activities and designing performance indicators for information services : case study : academic libraries in Malaysia and neighbouring countries - Sabariyah Din; Rosna Taib 1947-, author; Awaluddin Mohamed Shaharoun; Badariah Borham, 1959- author; Malaysian Science and Technology Congress (1997 : Johor Bahru)
99